Histopathological characterization of primary cutaneous melanoma using infrared microimaging: a proof-of-concept study - Ly, E.; Cardot-Leccia, N.; Ortonne, J.-P.; Benchetrit, M.; Michiels, J.-F.; Manfait, M.; Piot, O. (British journal of dermatology (1951), 2010)
Summary Background  The diagnosis of malignant melanoma is based upon the histological evaluation of the lesion. As such, the morphological interpretation relies on the expertise of a dermatopathologist. Infrared microimaging is emerging as a new powerful tool to investigate tissue biochemistry. Infrared spectra probe the biochemical constitution of the sample and are real tissue‐specific spectroscopic fingerprints. Objectives  To assess the potential of infrared microimaging to aid in the analysis of tissue sections from primary cutaneous melanomas. Methods  Ten samples of melanoma sections from the main histological subtypes were investigated using infrared microimaging combined with multivariate statistical analyses. Results  This methodology yielded highly contrasted colour‐coded images that permitted to highlight tissue architecture without any staining. It was possible to discriminate tumour areas from normal epidermis automatically, and intratumoral heterogeneity as revealed by our approach was correlated with the aggressiveness of the tumour. Conclusions  This proof‐of‐concept study shows that infrared microimaging could help in the diagnosis of primary cutaneous melanoma.